Prescription contraception use: a cross-sectional population study of psychosocial determinants - Molloy, Gerard J (BMJ Open, 2015)
OBJECTIVE: Many forms of contraception are available on prescription only for example, the oral contraceptive pill (OCP) and long-acting reversible contraceptives (LARCs). In this analysis we aim to identify key determinants of prescription contraceptive use. DESIGN: Cross-sectional population survey. Data on sociodemographic indices, concerns about the OCP and perceived barriers to access were collected. SETTING: Data set constructed from a representative population-based telephone survey of community dwelling adults in the Republic of Ireland (RoI) PARTICIPANTS: 1515 women aged between 18 and 45 years MAIN OUTCOME MEASURE: Self-reported user of the OCP or LARCs (intrauterine contraception, contraceptive injections or subdermal contraceptive implants) in the previous 12 months. RESULTS: For at least some of the previous year, 35% had used the OCP and 14% had used LARCs, while 3% had used two or more of these methods. OCP users were significantly younger, more likely to be unmarried and had higher income than non-users. Overall, 68% agreed with the statement ‘that taking a break from long-term use of the contraceptive pill is a good idea’ and 37% agreed with the statement that ‘the OCP has dangerous side effects’ and this was the strongest predictor variable of non-use of the OCP. Intrauterine contraception users were significantly older, more likely to be married and had lower income than non-users. Injections or subdermal contraceptive implant users were significantly younger, less likely to be married, had lower income and were less likely to agree that taking a break from long-term use of the pill is a good idea than non-users. CONCLUSIONS: Prescription contraceptive use is sociodemographically patterned, with LARCs in particular being associated with lower incomes in the RoI. Concerns about the safety of the OCP remain prevalent and are important and modifiable determinants of contraceptive-related behaviour.